1990
DOI: 10.1016/s0022-5347(17)40084-x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunotherapy in Paraplegic Patients with Chronic Urinary Tract Infections: A Double-Blind, Placebo-Controlled Trial

Abstract: In a 6-month, double-blind, placebo-controlled clinical trial with cross-over, we investigated the efficacy and tolerance of an orally administered bacterial extract in 70 spinal cord injury patients with chronic lower urinary tract infections. In the treated patients, compared to those given placebo, there was a statistically significant decrease in the degree of bacteriuria, a considerably decreased incidence of infectious episodes and a lesser requirement for antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 13 publications
1
31
0
4
Order By: Relevance
“…The number of recurrences, confirmed in the trial by the presence of bacteriuria (germ count > 10_5/ml), was diminished in a statistically significant manner (p < 0.0005) during the 6-month period of the trial when com pared to the same period preceding the trial as shown in Such improvements, already reported in previous studies [9][10][11][12], are certainly related to a restoration of the cellular and humoral immune mechanisms which are often impaired in patients susceptible to infection [13].…”
Section: Resultssupporting
confidence: 74%
“…The number of recurrences, confirmed in the trial by the presence of bacteriuria (germ count > 10_5/ml), was diminished in a statistically significant manner (p < 0.0005) during the 6-month period of the trial when com pared to the same period preceding the trial as shown in Such improvements, already reported in previous studies [9][10][11][12], are certainly related to a restoration of the cellular and humoral immune mechanisms which are often impaired in patients susceptible to infection [13].…”
Section: Resultssupporting
confidence: 74%
“…One study [24] was excluded because, although double-blind, it dealt with a special group of patients: in a 6-month, double-blind, placebo-controlled clinical trial with cross-over, the authors administered the bacterial extract OM-89 in 70 spinal cord injury patients with chronic lower UTIs. Compared with patients given placebo, in the treated patients there was a statistically significant decrease in the degree of bacteriuria, a considerably decreased incidence of infectious episodes and a lesser requirement for antibiotics.…”
Section: Product 'A': Om-89 (Uro-vaxom ® )mentioning
confidence: 99%
“…84 Hagberg and colleagues have had some success with instillations of E. coli showing no recognised virulence factors (isolated from a patient with asymptomatic bacteriuria), in preventing symptomatic infection with patho- 85 Immunotherapy with orally administered extracts from E. coli has also been reported to be e ective in reducing the incidence of urinary tract infections in paraplegic patients. 86 …”
Section: Experimental Methods Of Preventionmentioning
confidence: 99%